Amorphous bimetallic sulfide material, preparation method, electrode material and application

By adopting amorphous bimetallic sulfide materials in the field of lithium and sodium ion batteries, combined with alkaline non-solvent phase separation and pre-oxidation sulfide carbonization processes, the problem of poor performance of materials in the prior art in sodium ion batteries is solved, and the electrochemical performance in both batteries is achieved.

CN119764362AActive Publication Date: 2025-04-04CHINA MACHINERY INT ENG DESIGN & RES INST
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411206491.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-04-04
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high electrochemical performance materials in the fields of lithium and sodium ion batteries, and the existing materials do not perform well in sodium ion battery applications.

Method used

Amorphous bimetallic sulfide material is used to separate phases by mixing metal salts and non-solvent liquids in an alkaline environment in dimethylformamide, and combined with pre-oxidation, sulfide carbonization and cooling processes, a nano-level amorphous bimetallic sulfide material is prepared.

Benefits of technology

It achieved good electrochemical performance in lithium and sodium ion batteries, broke through the theoretical capacity limit of a single metal element, and slowed down volume expansion through amorphous structure, improving electrochemical cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764362A_ABST
    Figure CN119764362A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and particularly discloses an amorphous bimetallic sulfide material, a preparation method, an electrode material and application. According to the preparation method, two metal elements with a certain synergistic effect are selected for preparing a DMF homogeneous polymer, an alkaline non-solvent induced phase separation method is combined, and the amorphous bimetallic sulfide material which can be applied to lithium and sodium ion batteries and is excellent in electrochemical performance is obtained by regulating and controlling pre-oxidation, sulfuration carbonization and cooling processes. Particularly, the two different metal elements can break through the theoretical capacity limit of a single metal element, and further breakthrough is achieved on the existing specific capacity limit; a step-by-step vulcanization and carbonization process is adopted, a stable and sufficient vulcanization process is firstly carried out, and then a short-time carbonization process is carried out; and after the carbonization process is completed, the cooling process is carried out immediately, so that the crystal is difficult to nucleate, crystallize and grow, the nano-scale amorphous particles are prepared, and the volume expansion rate is reduced fundamentally and structurally.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and specifically discloses an amorphous bimetallic sulfide material for making an electrode material, a preparation method, an electrode material and an application thereof. Background Art

[0002] As the most promising rechargeable batteries in energy storage devices, lithium and sodium ion batteries have received extensive attention and research. Electrode materials, as the core components of energy storage devices, carry electrochemical reactions and play a role in the transmission of ions and electrons. As an important component of electrode materials, the research and development of negative electrode materials is particularly important. By selecting appropriate negative electrode materials, it is possible to improve electrochemical performance while reducing costs.

[0003] The invention application with publication number CN117747849A discloses a multi-scale electrode and method for a flow battery based on non-solvent induced phase separation, specifically comprising: S1, adding dimethylformamide solvent to a mixed powder of polyacrylonitrile and polyvinyl pyrrolidone, heating and stirring in an oil bath to obtain a clear light yellow viscous solution; S2, pouring the obtained light yellow viscous solution evenly into a mold, first pre-treating the mold containing the solution, and then immersing it in a constant temperature water bath for phase separation to obtain a small-scale pore polymer matrix for preparing a porous electrode; S3, wiping the obtained polymer matrix dry and clamping it between two alumina ceramic sheets, placing the completely dried polymer matrix and the two alumina ceramic sheets clamped on both sides of the polymer matrix into a muffle furnace for pre-carbonization, and then transferring them together into a tubular furnace for carbonization treatment under a nitrogen environment; S4, based on the simulation results of the pore scale model, perforating the product obtained in S3 by infrared laser to achieve the processing of large-scale pores in the multi-scale electrode, thereby completing the preparation of the multi-scale electrode. This invention is based on non-solvent induced phase separation technology and infrared laser perforation technology, combined with the typical symmetrical structure of the cross-type flow channel, and proposes a new multi-scale electrode structure. This invention belongs to the field of liquid flow batteries and cannot effectively solve the problems faced in the field of lithium and sodium ion batteries.

[0004] The invention application with publication number CN115602845A discloses a modified graphene negative electrode material and a preparation method thereof, a negative electrode plate and a battery. The method specifically comprises: mixing and stirring the modified graphene obtained by esterification modification of carboxylated graphene, polyvinyl pyrrolidone and tetrahydrofuran to obtain a homogeneous solution; adding glacial acetic acid to adjust the pH of the homogeneous solution to a weak acidity, gradually adding a mixed solution of titanate and anhydrous ethanol to form a gelation system, and using a non-solvent induced phase separation method to precipitate a porous graphene precipitate with titanium dioxide deposited in a porous structure. The selected modified graphene material has a good performance improvement only in the application field of lithium-ion batteries, and does not involve the field of sodium-ion batteries.

[0005] Xiao Tianyi from Central South University published a paper in the Journal of Energy Storage titled "In-situ growth of flake SnS in three-dimensional hierarchical porous carbon boosting lithium storage performance, Journal of Energy Storage, Volume 78, 2024, 109897, ISSN 2352-152X". The paper disclosed a crystalline tin sulfide grown on the surface of a hierarchical porous carbon matrix, and achieved relatively excellent performance in the field of lithium-ion batteries. As a lithium-ion battery in the 0.1Ag -1 After 100 cycles, it can maintain 917.6 mAh g -1 The discharge specific capacity of the battery is good, but the final product in this paper has a high carbon content and generates a single crystalline tin sulfide, which has insufficient active sites for effective charge and discharge.

[0006] In summary, there is an urgent need for a material that can be used in both lithium and sodium ion batteries and has good electrochemical properties to solve the problems existing in the prior art. Summary of the invention

[0007] The object of the present invention is to provide an amorphous bimetallic sulfide material which can be used in both lithium and sodium ion batteries and has good electrochemical performance after being made into an electrode material. The specific technical scheme is as follows:

[0008] An amorphous bimetallic sulfide material, the chemical structure of which is expressed as MS / NS@HPC, wherein: M and N are two different transition metals among V, Cr, Cu, Zr, Sn, Zn, Fe, Co, Mo, Ti, Ni and Mn; MS / NS is a composite amorphous bimetallic sulfide material; HPC is a hierarchical porous carbon matrix, which is a hierarchical porous structure under SEM observation.

[0009] Preferably, the mass of HPC does not exceed 25% of the total mass of the composite amorphous bimetallic sulfide material; the amorphous bimetallic sulfide material is 8-12 nm particles located inside the hierarchical porous carbon matrix.

[0010] The present invention also discloses a method for preparing an amorphous bimetallic sulfide material, comprising the following steps:

[0011] Step 1, preparing a DMF homogeneous polymer, specifically: adding M metal salt and N metal salt in proportion to dimethylformamide and stirring evenly to obtain a first mixed solution; adding polyacrylonitrile and polyvinyl pyrrolidone to the first mixed solution in sequence under stirring conditions to obtain a DMF homogeneous polymer;

[0012] Step 2, preparing a hierarchical porous precursor, specifically: adding a DMF homogeneous polymer to a non-solvent liquid in an alkaline environment under stirring conditions, and washing and drying after the addition is completed to obtain a hierarchical porous precursor;

[0013] Step 3: preparing an amorphous bimetallic sulfide material, specifically comprising:

[0014] Step 3.1, pre-oxidation treatment, specifically: pre-oxidation treatment of the graded porous precursor to obtain a pre-oxidized precursor;

[0015] Step 3.2, sulfurization and carbonization treatment, specifically: under the protection of inert gas, firstly subject the pre-oxidized precursor to a sulfur source for sulfurization reduction reaction at a temperature condition of T1, and then subject it to carbonization treatment at a temperature condition of T2 to obtain a sulfurized and carbonized product; T1+340°C<T2;

[0016] Step 3.3, cooling treatment, specifically: cooling the product after sulfidation and carbonization with a cooling agent to obtain an amorphous bimetallic sulfide material; the chemical structure of the amorphous bimetallic sulfide material is expressed as MS / NS@HPC, wherein: M and N are two different transition metal elements among V, Cr, Cu, Zr, Sn, Zn, Fe, Co, Mo, Ti, Ni and Mn.

[0017] The present invention selects two metal elements with certain synergistic effects to prepare DMF homogeneous polymers, combines a non-solvent liquid in an alkaline environment as a reagent for a non-solvent induced phase separation method, and then obtains an amorphous bimetallic sulfide material that can be applied to lithium and sodium ion batteries and has good electrical properties by regulating the pre-oxidation, sulfurization carbonization and cooling processes. In particular, the two different metal elements can break through the theoretical capacity limit of a single metal element and achieve further breakthroughs in the existing specific capacity limit; a step-by-step sulfurization and carbonization process is adopted, first a stable and sufficient sulfurization process is carried out, followed by a shorter carbonization process; a cooling process is immediately carried out after the carbonization process is completed, so that it is difficult for crystals to nucleate and crystallize, thereby preparing nano-scale amorphous particles and reducing the volume expansion rate from a fundamental structural perspective.

[0018] Preferably, in the step 1: the M metal salt and the N metal salt are two of ferrous chloride tetrahydrate, stannous chloride dihydrate, nickel chloride hexahydrate, cupric chloride dihydrate, zinc sulfate heptahydrate, vanadium sulfate, cobalt chloride hexahydrate, zirconium nitrate trihydrate, chromium chloride hexahydrate, molybdenum trichloride, titanium oxysulfate and manganese chloride tetrahydrate, the molar ratio of the M element in the M metal salt to the N element in the N metal salt is 1:1; the mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is 4:1; the total mass of polyacrylonitrile and polyvinyl pyrrolidone is half the mass of the composite amorphous bimetallic sulfide material MS / NS.

[0019] Preferably, in the step 2: the non-solvent liquid in the alkaline environment contains at least one of potassium hydroxide, sodium hydroxide, ammonia water, sodium carbonate and sodium bicarbonate; the DMF homogeneous polymer is added to the non-solvent liquid in the alkaline environment at a drop rate of 1-2 ml / min; the rotation speed during stirring is 300-400 rpm; washing is specifically performed by repeatedly washing with deionized water for 3-6 times; and drying is specifically performed by freeze drying for 24h-48h using a freeze dryer.

[0020] Preferably, in step 2, the graded porous precursor comprises a graded porous carbon matrix and metal oxides and / or metal hydroxides enclosed in the graded porous carbon matrix, the metal oxide comprises at least one of M oxide and N oxide, and the metal hydroxide comprises at least one of M hydroxide and N hydroxide.

[0021] Preferably, in the step three: during the pre-oxidation treatment, the temperature is increased to 260°C-270°C at a heating rate of 0.5°C-1°C / min and kept warm for 2h-3h; during the sulfurization and carbonization treatment: the temperature is increased to 220°C-300°C at a heating rate of 1°C-2°C / min and kept warm for 0.5h-1h for sulfurization reduction reaction, the sulfur source is at least one of thiourea and sulfur powder, and the mass ratio of the sulfur source to the pre-oxidized precursor is 5:1; the carbonization treatment is terminated after the temperature is increased to 650°C-800°C at a heating rate of 3°C-5°C / min; the inert gas is at least one of argon, hydrogen argon and nitrogen, and the argon accounts for 95% and the hydrogen accounts for 5% in the hydrogen argon; during the cooling treatment: the sulfurization and carbonization product is placed in a container and liquid nitrogen is poured into the container for sealing, and cooled at a cooling rate of 50°C-80°C / second.

[0022] Preferably, when thiourea is used for the vulcanization process, the thiourea is placed upstream of the tubular furnace, and the pre-oxidized precursor is placed downstream of the tubular furnace, and the hydrogen sulfide-containing substance generated by the decomposition of thiourea diffuses downstream with the continuously introduced inert gas, and undergoes a sulfidation-reduction reaction with the pre-oxidized precursor; when sulfur powder is used for the vulcanization process, the sulfur powder and the pre-oxidized precursor are evenly mixed and placed downstream of the tubular furnace, and the sulfur powder and the pre-oxidized precursor undergo a sulfidation-reduction reaction.

[0023] The invention also discloses an electrode material, which is made from the amorphous bimetallic sulfide material obtained by the above preparation method.

[0024] The present invention also discloses an application of the electrode material, wherein the electrode material is applied to a lithium ion battery and / or a sodium ion battery.

[0025] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0027] FIG. 1( a ) is a SEM image of the amorphous bimetallic sulfide material of Example 1 of the present invention;

[0028] FIG1( b ) is a SEM image of the amorphous bimetallic sulfide material in Comparative Example 1;

[0029] FIG. 2( a ) is a graph showing the electrode material in 2Ag in Example 1 of the present invention. -1 The lithium-ion battery cycle performance curve at the current density;

[0030] Figure 2(b) shows the electrode material in Example 1 at 2Ag -1 The lithium-ion battery cycle performance curve at the current density of;

[0031] FIG. 3( a ) is a graph showing the electrode material in Example 1 of the present invention at 1Ag -1 The sodium ion battery cycle performance curve at the current density of;

[0032] Figure 3(b) shows the electrode material in Example 1 at 1Ag -1 The sodium ion battery cycle performance curve at the current density of;

[0033] FIG4( a) is a thermogravimetric analysis graph of Example 1 of the present invention;

[0034] FIG4( b ) is a thermogravimetric analysis curve of Comparative Example 1. DETAILED DESCRIPTION

[0035] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0036] Embodiment 1:

[0037] An amorphous bimetallic sulfide material, the chemical structure of which is expressed as MS / NS@HPC, wherein: M and N are two different transition metals among V, Cr, Cu, Zr, Sn, Zn, Fe, Co, Mo, Ti, Ni and Mn; MS / NS is a composite amorphous bimetallic sulfide material; HPC is a graded porous carbon matrix, and the mass of HPC does not exceed 25% of the total mass of the composite amorphous bimetallic sulfide material; the amorphous bimetallic sulfide material is 8-12nm particles, which are located inside the graded porous carbon matrix.

[0038] The preparation method of the amorphous bimetallic sulfide material comprises the following steps:

[0039] Step 1, preparing a DMF homogeneous polymer, specifically: adding M metal salt and N metal salt in proportion to dimethylformamide and stirring evenly to obtain a first mixed solution; adding polyacrylonitrile and polyvinyl pyrrolidone to the first mixed solution in sequence under stirring conditions to obtain a DMF homogeneous polymer;

[0040] In this embodiment, the molar ratio of the M metal salt to the N metal salt is preferably 1:1, specifically 2.25g of stannous chloride dihydrate and 2.07g of zinc sulfate heptahydrate are used; dimethylformamide (DMF) is 25ml; the dimethylformamide is rapidly dissolved at a stirring speed of 600rpm at room temperature until the dimethylformamide becomes clear and transparent again to obtain a first mixed solution; while maintaining sufficient stirring, polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) are added in sequence, and the mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is 4:1; the total mass of polyacrylonitrile and polyvinyl pyrrolidone is half the mass of the composite amorphous bimetallic sulfide material MS / NS, and preferably 0.6g of polyacrylonitrile (PAN) and 0.15g of polyvinyl pyrrolidone (PVP) are added in sequence here, and then the mixture is placed in a water bath at 80°C for 40min of water bath heating and rapid stirring, and the speed is maintained at 600rpm; after the water bath program ends, the homogeneous polymer is placed at room temperature and continues to be fully stirred and mixed for 12h to obtain a DMF homogeneous polymer.

[0041] Step 2: preparing a hierarchical porous precursor, specifically: adding a DMF homogeneous polymer to a non-solvent liquid in an alkaline environment under stirring conditions, and washing and drying after the addition is completed to obtain a hierarchical porous precursor.

[0042] Preferably, in this embodiment: a DMF homogeneous polymer is dripped into a 0.5 mol / L potassium hydroxide liquid at a speed of 1 ml / min using a 0.5 mm caliber needle. During this process, continuous stirring is required to prevent polymer agglomeration, and the stirring speed is maintained at 400 rpm. After all the DMF homogeneous polymer is dripped, stirring is stopped and the alkaline non-solvent liquid in the container is removed. The primary product retained in the container is repeatedly washed with deionized water for 3 times, and then freeze-dried for 24 hours using a freeze dryer to finally obtain a graded porous precursor, and the hydroxides corresponding to the tin and iron metals are sealed in the polyacrylonitrile precursor skeleton.

[0043] Step 3: preparing an amorphous bimetallic sulfide material, specifically comprising:

[0044] Step 3.1, pre-oxidation treatment, specifically: pre-oxidation treatment is performed on the graded porous precursor to obtain a pre-oxidized precursor.

[0045] In this embodiment, in order to ensure that the morphology of the hierarchical porous precursor is not destroyed and collapsed during the high-temperature calcination process, the hierarchical porous precursor is pre-oxidized using a muffle furnace, and the temperature is raised to 260° C. at a heating rate of 0.5° C. / min and kept at this temperature for 2 hours.

[0046] Step 3.2, sulfurization and carbonization treatment, specifically: under the protection of inert gas, firstly subject the pre-oxidized precursor to a sulfur source sulfurization reduction reaction at temperature condition T1, and then subject it to carbonization treatment at temperature condition T2 to obtain a sulfurized and carbonized product; T1+340℃<T2.

[0047] In this embodiment, thiourea (CH4N2S) is added to the pre-oxidized bimetallic precursor at five times the mass, and the pre-oxidized precursor is placed upstream of the tube furnace and the pre-oxidized precursor is placed downstream of the tube furnace. Under the protection of argon, the temperature is raised to 250°C at a heating rate of 1°C / min and kept for 0.5h to complete the sulfurization treatment. Then the heating rate is changed and the temperature is raised to 750°C at a heating rate of 3°C / min to complete the carbonization treatment.

[0048] Step 3.3, cooling treatment, specifically: cooling the product after sulfidation and carbonization with a cooling agent to obtain an amorphous bimetallic sulfide material.

[0049] Preferably, in this embodiment, in order to ensure the successful preparation of the amorphous structure, the product is rapidly cooled by liquid nitrogen after the tube furnace insulation program is completed.

[0050] The electrode material preparation technology used to make the electrode material using the above-mentioned amorphous bimetallic sulfide material is a conventional technology, and the purpose is to prove the feasibility of self-growing amorphous bimetallic sulfide materials inside the hierarchical porous carbon matrix through the above-mentioned preparation method based on data examples.

[0051] Preparation process of negative electrode slurry: take the final product and grind it into powder through a mortar, and grind it with acetylene black (ACET) and polyacrylic acid (PAA) at a mass ratio of 7:2:1 for 40 minutes, then add N-methylpropiolide (NMP) solution drop by drop, and stir at room temperature for 12 hours to form a working electrode slurry. The negative electrode slurry is evenly coated on the clean copper foil and surface by a coating machine, and the average mass load of the battery electrode is controlled by controlling the coating thickness. Then vacuum dry it in a vacuum drying oven at 90°C for 12 hours. After complete drying, use a manual punching machine to punch the copper foil into round electrodes for use.

[0052] The assembly of lithium and sodium ions uses button battery cases with specifications of CR-2016, and the entire assembly process is carried out in a glove box under an argon atmosphere (water and oxygen content is less than 0.5ppm). The lithium-ion half-cell consists of a bimetallic sulfide electrode as a working electrode, a metal lithium sheet as a counter electrode, and a diaphragm (porous polyethylene). The lithium-ion battery electrolyte added during the assembly process is lithium hexafluorophosphate (LiPF6), to which vinylene carbonate (VC) with a mass ratio of 1.0% and ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate (EC:DEC:EMC) with a volume ratio of 1:1:1 are added. The sodium ion half-cell is composed of a bimetallic sulfide as a working electrode, a metal sodium sheet as a counter electrode, and a diaphragm (glass fiber). The sodium ion battery electrolyte added during the assembly process is sodium perchlorate (NaClO4), to which 5.0% fluoroethylene carbonate (FEC) is added in a mass ratio and ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate (EC:DEC:EMC) in a volume ratio of 1:1:1. Finally, the assembled battery is pressed and packaged by a battery packaging machine and left to stand for a period of time to allow the electrolyte to fully infiltrate (lithium ion batteries stand for 24 hours, sodium ion batteries stand for 5 hours).

[0053] Embodiment 2-3:

[0054] The difference between Example 2-3 and Example 1 is as shown in Table 1:

[0055] Table 1 Parameter statistics of Examples 1-3

[0056]

[0057] The SEM images of the amorphous bimetallic sulfide materials obtained in Examples 2 and 3 are similar to those in Example 1.

[0058] Comparative Example 1:

[0059] An amorphous bimetallic sulfide material, the preparation process is as follows:

[0060] The first step is to prepare a DMF homogeneous polymer:

[0061] 5 g of metal salt (specifically stannous chloride dihydrate) was added to 25 ml of dimethylformamide (DMF) and rapidly dissolved at room temperature at a stirring speed of 600 rpm until the dimethylformamide became clear and transparent again. While maintaining sufficient stirring, 2 g of polyacrylonitrile (PAN) and 0.5 g of polyvinyl pyrrolidone (PVP) were added in sequence, and then the mixture was placed in an 80°C water bath for 40 minutes of water bath heating and rapid stirring, with the speed maintained at 600 rpm. After the water bath process was completed, the homogeneous polymer was placed at room temperature and continued to be fully stirred and mixed for 12 hours.

[0062] Step 2: Preparation of hierarchical porous precursor:

[0063] After the complete mixing, the DMF homogeneous polymer is dripped into the deionized water at a speed of 1 ml / min using a 0.5 mm caliber needle. During this process, continuous stirring is required to prevent the polymer from agglomerating, and the stirring speed is maintained at 400 rpm. After all the DMF homogeneous polymers are dripped, the stirring is stopped and the deionized water in the container is removed. The primary product retained in the container needs to be repeatedly washed with deionized water for 3 times, and then freeze-dried for 24 hours using a freeze dryer to finally obtain a graded porous precursor, and the hydroxide corresponding to the tin metal is sealed in the polyacrylonitrile precursor skeleton.

[0064] Step 3: Preparation of amorphous bimetallic sulfide materials:

[0065] Step ①, pre-oxidation process: pre-oxidation treatment is performed on the graded porous precursor using a muffle furnace, specifically: heating to 260° C. at a heating rate of 0.5° C. / min and keeping the temperature for 2 h.

[0066] Step ②, sulfurization and carbonization process: add thiourea (CH4N2S) according to five times the mass of the pre-oxidized tin metal precursor, and place it upstream of the tube furnace and the pre-oxidized precursor downstream of the tube furnace. Under the protection of argon, heat directly to 550°C at a heating rate of 2°C / min and keep warm for 3h.

[0067] Step ③, cooling process: cooling with the furnace, specifically: natural cooling in a tubular furnace after the sulfurization and carbonization processes are completed, the purpose is to prepare a crystalline single metal sulfide for comparison.

[0068] The preparation of electrode material using the above-mentioned amorphous bimetallic sulfide material is carried out in the same manner as in Example 1.

[0069] Comparative Examples 2-5:

[0070] Comparative Examples 2-5 differ from Comparative Example 1 in that the following are shown in Table 2:

[0071] Table 2 Parameter statistics of comparative examples 1-5

[0072]

[0073]

[0074] The prepared negative electrode material Example 1 and Comparative Example 1 were subjected to phase analysis characterization and electrochemical performance testing, and the test results are as follows:

[0075] Combined with Figure 1(a) and Figure 1(b): It can be seen from Figure 1(a) that the amorphous tin zinc sulfide in Example 1 did not grow on the surface of the graded porous carbon matrix; it can be seen from Figure 1(b) that the crystalline stannous sulfide in Comparative Example 1 grew on the surface of the graded porous carbon matrix.

[0076] Combined with Figure 2(a) and Figure 2(b): Comparing Figure 2(a) and Figure 2(b), the lithium-ion battery at 2Ag -1 The cycle performance of 500 cycles in the embodiment and comparative example 1 was tested at a current density of , and it can be seen that no matter the first cycle charge and discharge capacity, the discharge specific capacity after 500 cycles, or the stability of the discharge specific capacity, the embodiment is superior to the comparative example.

[0077] Combined with Figure 3(a) and Figure 3(b): Comparing Figure 3(a) and Figure 3(b), the sodium ion battery at 1Ag -1 The cycle performance of 500 cycles in the embodiment and comparative example 1 was tested at a current density of , and it can be seen that no matter the first cycle charge and discharge capacity, the discharge specific capacity after 500 cycles, or the stability of the discharge specific capacity, the embodiment is superior to the comparative example.

[0078] Combined with Figure 4(a) and Figure 4(b): The carbon content in the amorphous bimetallic sulfide material obtained in Example 1 shown in Figure 4(a) is only 21.2%, which is much lower than the carbon content of 48.2% in the amorphous bimetallic sulfide material obtained in Comparative Example 1 shown in Figure 4(b). This fully illustrates that the alkaline non-solvent environment allows less metal ions to be lost, and most of them are sealed in the carbon matrix skeleton.

[0079] The prepared negative electrode material examples 1-3 and comparative examples 1-5 were subjected to phase analysis characterization and electrochemical performance testing, and the results are shown in Table 3 and Table 4:

[0080] Table 3 Electrochemical performance test data of Examples 1-3 and Comparative Examples 1-5

[0081]

[0082] Table 4 Phase analysis characterization data table of Examples 1-3 and Comparative Examples 1-5

[0083] Case / Characterization Crystal structure of the final product Thermogravimetric analysis of carbon content after vulcanization and carbonization process Example 1 Amorphous 21.2% Example 2 Amorphous 22.3% Example 3 Amorphous 19.4% Comparative Example 1 Crystalline 48.2% Comparative Example 2 Structural collapse 23.8% Comparative Example 3 Crystalline 22.6% Comparative Example 4 Crystalline 20.1% Comparative Example 5 Crystalline 24.7%

[0084] Combining Table 2, Table 3 and Table 4, we can see that:

[0085] The difference between Comparative Example 2 and Example 1 is that there is a single metal and no pre-oxidation step. The role of pre-oxidation is to prevent the collapse of the hierarchical porous structure formed in the precursor stage. Comparative Example 2 did not perform the pre-oxidation step. During the sulfurization and carbonization stages, the structure collapsed due to the excessively fast heating rate. In the end, there was no complete morphology structure, and no electrochemical performance test was performed. In Example 1, an alkaline non-solvent environment was used for the phase separation step, which can effectively inhibit the loss of metal ions, and they are finally sealed in the hierarchical porous precursor.

[0086] The difference between Comparative Example 3 and Example 1 is that the sulfurization and carbonization process is carried out in a one-step process. In Comparative Example 3, the sulfurization and carbonization process is carried out at a higher temperature for a longer time, resulting in crystal nucleation and crystallization growth, and finally forming a crystalline structure, and the electrochemical performance of lithium and sodium ion batteries is poor. In Example 1, the alkaline non-solvent environment is used for the phase separation step, which can effectively inhibit the loss of metal ions, and finally they are sealed in the hierarchical porous precursor.

[0087] The difference between Comparative Example 4 and Example 1 is that three kinds of metal salts are used. The addition of more metal elements in Comparative Example 4 has limited improvement on performance, and it is difficult to control the nucleation and growth of multiple metal sulfides, resulting in the formation of a crystalline structure and poor electrochemical performance of lithium and sodium ion batteries. In Example 1, an alkaline non-solvent environment is used for the phase separation step, which can effectively inhibit the loss of metal ions, and finally they are sealed in the hierarchical porous precursor.

[0088] The difference between Comparative Example 5 and Example 1 is that four metal salts are used. The addition of more metal elements in Comparative Example 5 has limited improvement on performance, and it is difficult to control the nucleation and growth of multiple metal sulfides, resulting in the formation of a crystalline structure and poor electrochemical performance of lithium and sodium ion batteries. It can be seen from Example 1 that the use of an alkaline non-solvent environment for the phase separation step can effectively inhibit the loss of metal ions, and they are finally sealed in the hierarchical porous precursor.

[0089] Based on the above, we can know that:

[0090] 1. Considering the application of lithium and sodium ion batteries: In the process of non-solvent induced phase separation in the present invention, an alkaline non-solvent environment is created, which can promote the hydrolysis of metal ions to form metal hydroxide / oxide products. These hydrolysis products will be sealed on the precursor skeleton, thereby preventing the large-scale loss of soluble metal ions. The final product after pre-oxidation, sulfidation, carbonization and cooling processes has more electrochemical reaction active sites and can be simultaneously applied to the fields of lithium and sodium ion batteries.

[0091] 2. Two different metal elements produce a synergistic effect: In the precursor preparation process of the present invention, two different metal elements are combined with a graded porous carbon matrix. Due to their different physical and chemical properties, the two different metal elements can break through the theoretical capacity limit of a single metal element and further break through the existing specific capacity limit.

[0092] 3. The size of the amorphous structure is nanometer-scale, which slows down the volume expansion: the amorphous bimetallic sulfide material formed by pre-oxidation, sulfurization carbonization and cooling process has a nanometer-scale size, which is several orders of magnitude smaller than the size of a single metal sulfide that is easy to grow to a micrometer size. It has a larger specific surface area and more reactive sites, and the electrochemical performance can be greatly improved. At the same time, it brings less impact during the volume expansion process, and the electrochemical cycle performance is better.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An amorphous bimetallic sulfide material, characterized in that: The chemical structure of the amorphous bimetallic sulfide material is expressed as MS / NS@HPC, wherein: M and N are two different transition metal elements among V, Cr, Cu, Zr, Sn, Zn, Fe, Co, Mo, Ti, Ni and Mn; MS / NS is a composite amorphous bimetallic sulfide material; HPC is a hierarchical porous carbon matrix.

2. The amorphous bimetallic sulfide material according to claim 1, characterized in that: The mass of HPC does not exceed 25% of the total mass of the composite amorphous bimetallic sulfide material; the amorphous bimetallic sulfide material is 8-12 nm particles located inside the hierarchical porous carbon matrix.

3. A method for preparing an amorphous bimetallic sulfide material, characterized in that: The following steps are involved: Step 1, preparing a DMF homogeneous polymer, specifically: adding M metal salt and N metal salt in proportion to dimethylformamide and stirring evenly to obtain a first mixed solution; adding polyacrylonitrile and polyvinyl pyrrolidone to the first mixed solution in sequence under stirring conditions to obtain a DMF homogeneous polymer; Step 2, preparing a hierarchical porous precursor, specifically: adding a DMF homogeneous polymer to a non-solvent liquid in an alkaline environment under stirring conditions, and washing and drying after the addition is completed to obtain a hierarchical porous precursor; Step 3: preparing an amorphous bimetallic sulfide material, specifically comprising: Step 3.1, pre-oxidation treatment, specifically: pre-oxidation treatment of the graded porous precursor to obtain a pre-oxidized precursor; Step 3.2, sulfurization and carbonization treatment, specifically: under the protection of inert gas, firstly subject the pre-oxidized precursor to a sulfur source for sulfurization reduction reaction at a temperature condition of T1, and then subject it to carbonization treatment at a temperature condition of T2 to obtain a sulfurized and carbonized product; T1+340°C<T2; Step 3.3, cooling treatment, specifically: cooling the product after sulfidation and carbonization with a cooling agent to obtain an amorphous bimetallic sulfide material; the chemical structure of the amorphous bimetallic sulfide material is expressed as MS / NS@HPC, wherein: M and N are two different transition metal elements among V, Cr, Cu, Zr, Sn, Zn, Fe, Co, Mo, Ti, Ni and Mn.

4. The preparation method according to claim 3, characterized in that: In the step 1, the M metal salt and the N metal salt are two of ferrous chloride tetrahydrate, stannous chloride dihydrate, nickel chloride hexahydrate, cupric chloride dihydrate, zinc sulfate heptahydrate, vanadium sulfate, cobalt chloride hexahydrate, zirconium nitrate trihydrate, chromium chloride hexahydrate, molybdenum trichloride, titanium sulfate and manganese chloride tetrahydrate, the molar ratio of the M element in the M metal salt to the N element in the N metal salt is 1:1; the mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is 4:1; the total mass of polyacrylonitrile and polyvinyl pyrrolidone is half the mass of the composite amorphous bimetallic sulfide material MS / NS.

5. The preparation method according to claim 3, characterized in that: In the step 2, the non-solvent liquid in the alkaline environment contains at least one of potassium hydroxide, sodium hydroxide, ammonia water, sodium carbonate and sodium bicarbonate; the DMF homogeneous polymer is added to the non-solvent liquid in the alkaline environment at a drop rate of 1-2 ml / min; the rotation speed during stirring is 300-400 rpm; washing is specifically performed by repeatedly washing with deionized water for 3-6 times; and drying is specifically performed by freeze drying for 24h-48h using a freeze dryer.

6. The preparation method according to claim 3, characterized in that: In step 2, the graded porous precursor comprises a graded porous carbon matrix and metal oxides and / or metal hydroxides enclosed in the graded porous carbon matrix, wherein the metal oxide comprises at least one of M oxide and N oxide, and the metal hydroxide comprises at least one of M hydroxide and N hydroxide.

7. The preparation method according to claim 3, characterized in that: In the step three: during the pre-oxidation treatment, the temperature is raised to 260°C-270°C in the air at a heating rate of 0.5°C-1°C / min and kept warm for 2h-3h; during the sulfurization and carbonization treatment: the temperature is raised to 220°C-300°C in an inert gas at a heating rate of 1°C-2°C / min and kept warm for 0.5h-1h to carry out a sulfurization reduction reaction, the sulfur source is at least one of thiourea and sulfur powder, and the mass ratio of the sulfur source to the pre-oxidized precursor is 5:1; the carbonization treatment is terminated after the temperature is raised to 650°C-800°C in an inert gas at a heating rate of 3°C-5°C / min; the inert gas is at least one of argon, hydrogen argon, and nitrogen, and the argon accounts for 95% and the hydrogen accounts for 5% in the hydrogen argon; during the cooling treatment: the sulfurization and carbonization product is placed in a container, liquid nitrogen is poured into the container for sealing, and cooled at a cooling rate of 50°C-80°C / second.

8. The preparation method according to claim 7, characterized in that: When thiourea is used for the sulfidation process, the thiourea is placed upstream of the tube furnace, and the pre-oxidized precursor is placed downstream of the tube furnace. The hydrogen sulfide-containing substance generated by the decomposition of thiourea diffuses downstream along with the continuously introduced inert gas, and undergoes a sulfidation-reduction reaction with the pre-oxidized precursor. When sulfur powder is used for the sulfurization process, the sulfur powder is mixed evenly with the pre-oxidized precursor and then placed downstream of the tube furnace, and the sulfur powder and the pre-oxidized precursor undergo a sulfurization reduction reaction.

9. An electrode material, characterized in that: The electrode material is made of the amorphous bimetallic sulfide material obtained by the preparation method described in claims 3-8.

10. Use of the electrode material according to claim 9, characterized in that: The electrode material is applied to lithium ion batteries and / or sodium ion batteries.

Citation Information

Patent Citations

  • Modified graphene negative electrode material and preparation method thereof, negative electrode plate and battery

    CN115602845A

  • Flow battery multi-scale electrode based on non-solvent induced phase separation and method

    CN117747849A

  • Submicron copper sulfide / sisal fiber carbon anode material for lithium ion battery and preparation method thereof

    CN104852016A

  • Preparation method of metal sulfide and carbon composite material and application of metal sulfide and carbon composite material in sodium ion battery

    CN106992293A

  • Drop-coating preparation method of hierarchical pore in-situ carbon electrode

    CN109607511A